Cationic Molecular Metal Chalcogenide Ligand-Passivated Colloidal Quantum Dots and Their Application to Suppressed Dark-Current Near-Infrared Photodetectors - Seo, Haewoon; Eun, Hyeong Ju; Choi, Donghyeuk; Na, Hyon Bin; Shim, Yeongseok; Heo, Junseok; Cho, Kyung Sang; Kim, Jong H.; Kim, Sang Wook (Advanced Materials Technologies, 2023)
The surface of colloidal-type quantum dots (QDs) is protected with surfactants to maintain their nanoscale size and dispersion in various solvents. Such protection is advantageous to the processability of the dots, but the surfactants also act as insulators, thereby adversely affecting the electrical properties of the resulting devices. Anion-type molecular metal chalcogenide complexes (MCCs) have been developed as an alternative to these surfactants. However, anionic ligands limit the charges of the resulting QDs to negative values; thus, additional processes are required to compensate for these charges. Herein, this work prepares cationic-type dimetal diselenium perchlorate MCCs (M2Se2(ClO4)2, M = Mn, Zn, and Sn) and applies them to stabilize colloidal QDs. The resulting M2Se2-PbS QDs are then used to fabricate near-infrared photodetectors (NIR-PDs). The devices exhibit remarkably suppressed dark current densities (JD) of as low as 4.92 × 10−10 A cm−2 when compared with PDs based on 1,2 ethandithiol-PbS (EDT-PbS) (JD = 1.41 × 10−8 A cm−2). In addition, the devices exhibit a high responsivity of 0.07 A W−1 in response to 950 nm NIR light signals, as well as an excellent specific detectivity of 5.66 × 1012 Jones at 950 nm. Finally, this work fabricates hybrid-type QD films using cationic and anionic MCC-PbS QDs and obtains a high external quantum efficiency (EQE) of 13.1%.
Keywords: Cationics; Colloidal quantum dots; Metal chalcogenide; Metal chalcogenide ligand; Molecular metals; Near infrared photodetectors; NIR photodetector; PbS quantum dots; Quantum dot; Surface ligands; metal chalcogenide ligands; NIR photodetectors; quantum dots; surface ligands